Probiotic Supplementation with S. salivarius K12 in Healthy Adults Increases Oral S. salivarius K12 in a Randomized, Double-Blind, Placebo-Controlled Study. (29th May 2020) - Smilowitz, Jennifer; Kalanetra, Karen; Meier, Anna; Kurudimov, Karina; Underwood, Mark; Mills, David
Abstract: Objectives: Streptococcus salivarius (S. salivarius) K12 supplementation in children and adults has been found to reduce the risk of recurrent pharyngitis, tonsillitis, otitis media caused by group A streptococci. The protection of S. salivarius K12 supplementation may in part result from its production of lantibiotic bacteriocins salivaricin A and B. Yet, studies have not reported the effect of supplementation on oral S. salivarius K12 levels or the broader salivary microbiome. The objective of this clinical trial was to determine how supplementation with S. salivarius K12 influences the oral microbiome. Methods: In a double-blind, placebo-control, prospective trial, 24 healthy adults were randomized to consume a probiotic powder (PRO) containing 7.8B CFU of L. acidophilus, 8.25B CFU of B. lactis, and 2B CFU of S. salivarius K12 (n = 12) or a placebo-control powder (CON) (n = 12) for fourteen consecutive days. Saliva samples were collected at baseline, at the end of the fourteen-day supplementation period and two weeks post-supplementation. Oral S. salivarius K12 and total bacteria were quantified by QPCR and the oral microbiome was measured using 16s rRNA amplicon sequencing. Results: Supplementation with S. salivarius K12 significantly increased salivary S. salivarius K12 by 5 logs compared to baseline for the PRO group ( P  < 0.0005) and returned to baseline 2-weeks post-supplementation. Compared with the CON group, salivary S. salivarius K12 was 5 logs higher in the PRO group at the end of the supplementation period ( P  < 0.001). Neither time nor supplementation influenced the oral microbiome. The supplement was well-tolerated. Conclusions: Supplementation with a probiotic containing S. salivarius K12 for two weeks significantly increased levels of salivary S. salivarius K12 by 5 logs but had no effect on the overall oral microbiome measured by 16s rRNA amplicon sequencing. Funding Sources: Renew Life funded this research but had no part in the analysis or interpretations of the study findings.